2017
DOI: 10.1530/joe-17-0023
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to endocrine disruptors during adulthood: consequences for female fertility

Abstract: Endocrine disrupting chemicals are ubiquitous chemicals that exhibit endocrine disrupting properties in both humans and animals. Female reproduction is an important process, which is regulated by hormones and is susceptible to the effects of exposure to endocrine disrupting chemicals. Disruptions in female reproductive functions by endocrine disrupting chemicals may result in subfertility, infertility, improper hormone production, estrous and menstrual cycle abnormalities, anovulation, and early reproductive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(167 citation statements)
references
References 174 publications
(233 reference statements)
1
150
0
2
Order By: Relevance
“…Thus, Hg may induce feminine infertility by increasing the prolactin secretion—analogous to the dopamine effect at the pituitary and midbrain level, with negative effects on galactopoiesis and female genitalia . Xenobiotics such as Hg, xenoestrogens, and synthetic oestrogens are endocrine disruptors present in most commercial foods, plastic products, tap water, plastic water glass, cosmetics, cleaning products, clothes detergents, paints, pesticides and insecticides . Careful identification and reducing of endocrine disruptors, including Hg exposures in everyday life, are essential to protect reproductive capacity.…”
Section: Mercury Exposure and Fertility: General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Hg may induce feminine infertility by increasing the prolactin secretion—analogous to the dopamine effect at the pituitary and midbrain level, with negative effects on galactopoiesis and female genitalia . Xenobiotics such as Hg, xenoestrogens, and synthetic oestrogens are endocrine disruptors present in most commercial foods, plastic products, tap water, plastic water glass, cosmetics, cleaning products, clothes detergents, paints, pesticides and insecticides . Careful identification and reducing of endocrine disruptors, including Hg exposures in everyday life, are essential to protect reproductive capacity.…”
Section: Mercury Exposure and Fertility: General Aspectsmentioning
confidence: 99%
“…19,96 Xenobiotics such as Hg, xenoestrogens, and synthetic oestrogens are endocrine disruptors present in most commercial foods, plastic products, tap water, plastic water glass, cosmetics, cleaning products, clothes detergents, paints, pesticides and insecticides. 97 Careful identification and reducing of endocrine disruptors, including Hg exposures in everyday life, are essential to protect reproductive capacity. An analysis of the relevance between the concentration of toxic elements and reproductive health in women with reproductive disorders has reported that the probability of mature oocytes is oppositely proportional to the Hg concentration in the hair (RR = 0.81, 95% CI: 0.70-0.95).…”
Section: Mercury Exposure and Fertilit Y: General Aspectsmentioning
confidence: 99%
“…Additional studies in younger women need to be conducted before excluding POPs and PFASs as risk factors in the general population. The suggestion that POPs may cause reproductive abnormalities in women [45], which is related to breast cancer risk, should also be further studied. Our results are also limited by the relatively small sample size and the inclusion of only non-Hispanic white women.…”
Section: Discussionmentioning
confidence: 99%
“…There is concern about the effects of EDCs on reproductive functions and development, as the classical targets of EDCs are nuclear receptors, including estrogen receptors. EDCs, such as 4‐nonylphenol (NP), bisphenol A (BPA) and butyl benzyl phthalate (BBP) (Figure ), are known to mimic estrogen in their actions (Giulivo, Lopez de Alda, Capri, & Barceló, ; Rattan et al, ). However, data on the effects of EDCs on estrogen metabolism in vivo are comparatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…& Barceló, 2016; Rattan et al, 2017). However, data on the effects of EDCs on estrogen metabolism in vivo are comparatively scarce.…”
mentioning
confidence: 99%